The effect of three-month topical testosterone gel application on semen quality in men with oligozoospermia and low serum testosterone levels - I. Thanaboonyawat; P. Chera-aree; S. Petyim; R. Choavaratana; P. Laokirkkiat (IMR Press, 2020)
Objective: The effects of daily topical application of testosterone gel on semen characteristics in infertile men with oligozoospermia and hypogonadism were assessed. Methods: Sixteen infertile men were included in this prospective study. A daily morning application of 25 mg transdermal testosterone (T) gel was used for 3 months. Semen parameters, serum follicular stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E) and T levels, and seminal plasma E and T levels were measured before treatment and once monthly for three months during the therapy. Results: The baseline median sperm concentration was 5.5 × 106/mL. Median sperm concentrations at the first, second and third months were 9 × 106, 8 × 10 6, and 4 × 106/mL, respectively. The sperm concentrations at the first and second months after starting therapy significantly (p < 0.001) increased compared with the baseline. However, sperm volume, pH, motility, viability and morphology were similar to baseline. Serum T significantly (p < 0.001) increased, while serum FSH significantly (p < 0.001) decreased from baseline. Seminal T and T/E ratios were raised significantly (p = 0.008 and p = 0.004, respectively) after gel application, whereas the seminal E level was not affected. Conclusions: Daily 25 mg T gel applications for oligospermic infertile men with hypogonadism increased the sperm concentration at the first and second months and raised the serum T level to the normal adult male range. Nevertheless, the sperm concentration had a decreasing trend after the third month.